LINEARITAS KALIMAT DALAM PARAGRAF KARANGAN ILMIAH MAHASISWA UNIVERSITAS NEGERI MALANG - Noorliana Noorliana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2012)
The study is aimed at revealing the sentence linearity of paragraph developed by college students, whether they show good or poor linearity. Also to describe the factors of poor linearity, as well as the order of pattern available in each pair of linear sentences. In general, the study applies the descriptive-qualitative method, and to analyze the relation between sentences it uses the micro-structural method. The research result shows that most paragraphs contain sentences of poor linearity. The causal factors are the ideas of bias, skip, accumulation, repetition, as well as false choice. Also, missing sentence constituents, and inconsistent use of lexicon (words and terminologies). Keywords: sentence linearity, paragraph, scientific writing.